The Influence of Product Innovation and Digital Marketing on Business Performance through Competitive Advantage in the Pet Supply Industry - Benedicta Evienia Prabawanti; Melinda Kang (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The increasing demand for pet rabbits has driven high consumer interest in pet supplies, creating both opportunities and challenges for businesses to develop sustainable competitive advantages. This study analyzes the influence of Product Innovation and Digital Marketing on SkinnyFat Factory's Business Performance, with Competitive Advantage as a mediating variable. A quantitative approach was employed, using an online questionnaire distributed to 150 respondents selected through purposive sampling. Respondents were consumers who had purchased or provided SkinnyFat Factory products for their pets. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 and bootstrapping techniques. The findings indicate that Product Innovation and Digital Marketing have a positive and significant impact on Business Performance (p < 0.05). Both variables also significantly influence Competitive Advantage, which mediates its effect on Business Performance. This study contributes to the literature by addressing a research gap: while previous studies have explored innovation and digital marketing in MSMEs, few have examined the mediating role of competitive advantage in a niche market such as pet supplies. Its novelty lies in mapping the relationship between innovation, digital marketing, and competitive advantage to improve business performance. This insight underscores the importance of continuous innovation and a targeted digital marketing strategy for maintaining long-term competitiveness and growth.